Supportive care in advanced chronic kidney disease: Withholding and withdrawing dialysis therapy - Belino,C (2018)
Over the latest few decades, dialysis has been offered to older and more complex patients. This treatment can increase the symptom burden and also add new symptoms that can have a profound impact in frail and/or elderly patients with multiple comorbidities. A quality of life approach may be more desirable than a quantity of life approach in these cases. Around the world, some countries have endorsed programs of shared decisionmaking process and advanced care planning for end-stage renal disease, with creation of goal-directed protocols. Alignment with palliative care programs to develop structured approaches is the key to successful outcomes. Reforms in medical education are needed to address current necessities in these areas. This article summarizes current knowledge regarding decision making and palliative care in end-stage renal disease.